A Novel Self‐Assembled Cobalt‐Free Perovskite Composite Cathode with Triple‐Conduction for Intermediate Proton‐Conducting Solid Oxide Fuel Cells. (30th September 2022) - Tong, Hua; Fu, Min; Yang, Yang; Chen, Fanglin; Tao, Zetian
Abstract: A traditional composite cathode for proton‐conducting solid oxide fuel cells (H‐SOFCs) is typically obtained by mixing cathode materials and proton conducting electrolyte of BaCe0.7 Y0.2 Zr0.1 O3–δ (BZCY), providing chemical and thermal compatibility with the electrolyte. Here, a series of triple‐conducing and cobalt‐free iron‐based perovskites as cathodes for H‐SOFCs is reported. Specifically, BaCe x Fe1– x O3–δ ( x  = 0.36, 0.43, and 0.50) shows various contents of two single phase perovskites with an in situ heterojunction structure as well as triple conductivity by tailoring the Ce/Fe ratios. The cell performance with the optimized BaCe0.36 Fe0.64 O3–δ (BCF36) cathode composition reaches 1056 mW cm −2 at 700 °C. Moreover, a record cell performance of 1525 mW cm −2 at 700 °C is obtained by modifying the BCF36 cathode microstructure through a spraying method, demonstrating high promise with Co‐free cathodes for H‐SOFCs. Abstract : A BaCe x Fe1– x O3–δ composite cathode with a heterojunction structure is applied for proton‐conducting solid oxide fuel cells. Oxygen reduction reactivity can be significantly enhanced by tailoring the Ce/Fe ratios. A cell power output of 1525 mW cm –2 at 700 °C is achieved by using a spray method to optimize the cathode microstructure.